Sequential Treatment with Activin and Hepatocyte Growth Factor Induces FOXM1 to Promote Colorectal Cancer Liver Metastasis - Hong Peng; Ting Ye; Lei Deng; Xiaofang Yang; Zheng Jiang; Jinjun Guo (Canadian Journal of Gastroenterology and Hepatology)
Background. Cancer stem cells (CSCs) are involved in liver metastasis in colorectal cancer (CRC). Activin and hepatocyte growth factor (HGF) are important regulators of stem cell properties. This study was performed to explore the effect of activin and HGF on CRC invasion and metastasis. The key genes involved in the action of activin and HGF in CRC were identified. Methods. HCT116 CRC cells were sequentially treated with activin and HGF and examined for migration and invasion in vitro and liver metastasis in vivo. RNA sequencing was performed to identify differentially expressed genes in response to activin and HGF. Results. Sequential treatment with activin and HGF-enhanced CRC cell migration, invasion, and metastasis. CXCR4 and AFP expressions were increased by activin and HGF treatment. Knockdown of FOXM1 blocked liver metastasis from HCT116 cells pretreated with activin and HGF and suppressed CXCR4 and AFP expression. Activin alone increased the mRNA and protein expression of FOXM1. In contrast, HGF alone enhanced the phosphorylation of FOXM1, without altering the total protein level of FOXM1. SMAD2 was required for activin-mediated FOXM1 induction. FOXM1 transactivated CXCR4 by directly binding to the promoter of CXCR4. Additionally, CXCR4 regulated AFP expression through the NF-κB pathway. Conclusions. Sequential treatment with activin and HGF accelerates CRC invasion and liver metastasis, which involves the upregulation and activation of FOXM1 and induction of CXCR4 and AFP.